Team Games Tournament Implementation in Enhancing Students’ Arabic Vocabulary: A Lesson from Islamic High Schools - Sari, Winda; Haeruddin, Haeruddin; Ridwan, Muhammad; Haeriyyah (JOLLT Journal of Languages and Language Teaching, 2026)
Mastery of Arabic vocabulary is a fundamental requirement that supports students’ abilities in listening, speaking, reading, and writing. However, many learners continue to struggle due to limited instructional variety and teacher-centered practices that reduce engagement and learning motivation. This issue is particularly evident among Grade XI students at MA PPM Tana Toraja, whose low vocabulary mastery negatively affects their ability to comprehend texts and use Arabic actively. While previous studies have emphasized the potential of cooperative learning strategies, limited empirical research focuses on the application of the Team Games Tournament (TGT) method in Arabic vocabulary instruction within boarding school contexts. To address this gap, the present study examines the effectiveness of the TGT method in enhancing students’ Arabic vocabulary mastery. Employing a pre-experimental one-group pre-test and post-test design, the study involved 17 students selected through purposive sampling. Data were collected using vocabulary tests, observation sheets, and student perception questionnaires, and analyzed through descriptive statistics, normality testing, and paired-samples t-test. The findings show a substantial improvement, with the mean score increasing from 47.06 on the pre-test to 84.41 on the post-test, and the t-test indicating a statistically significant difference (p < 0.001). These results demonstrate that the collaborative, game-oriented, and competitive elements of TGT effectively increase students’ motivation, participation, and vocabulary retention. Overall, the study concludes that the TGT method is an effective, engaging, and practical approach for improving students’ Arabic vocabulary mastery.